DAMPAK STIGMA NEGATIF PENYINTAS COVID – 19 DI RUMAH SAKIT LAPANGAN DARURAT (RSLD) B MANADO - Lumowa, Fresy (Lasalle Health Journal, 2022)
Introduction: Covid-19 first entered Indonesia in March 2019, the spread of this virus was very fast because of the fast pollution. This virus attacks the respiratory system and is very easily exposed to people who have a weak immune system, so that the health effects when exposed to this virus are very heavy and under certain conditions, resulting in death. Because of its rapid spread and stigma from the exposure of this virus is very frightening, so Covid-19 does not only have an impact on physical health, but has an impact on the mental health of the survivors of Covid-19, due to the negative stigma of the community Objective: To find out the impact of the negative stigma of Covid's survivors - 19 after being treated at the Covid-19 B Emergency Field Hospital (EFH). Method: Using a qualitative method with in-depth interview techniques to 7 informants. Results: Covid Survival - 19 After undergoing isolation at the Emergency Field Hospital (EFH) Covid-19 B Manado experienced the impact of psychological problems from the community and coworkers when returning to their activities, even though the survivor had been declared cured with negative PCR results and had undergone insulation for 14 days at the Emergency Field Hospital (EFH) Covid-19 B Manado. The lack of clear public knowledge about the spread of the Covid-19 virus causes negative stigma to the survivors of Covid-19 can occur. Conclusion: After undergoing isolation from exposure to Covid-19, survivors experience the impact of negative stigma such as low self-esteem, feeling ostracized, blaming themselves, even anxiety and psychological pressure then intimidation so that survivors blame themselves and withdraw from society.